Achieving stable interface for lithium metal batteries using fluoroethylene carbonate-modified garnet-type Li6.4La3Zr1.4Ta0.6O12 composite electrolyte. (1st April 2023) - Wang, Qiujun; Su, Ya; Zhu, Weiqi; Li, Zhaojin; Zhang, Di; Wang, Huan; Sun, Huilan; Wang, Bo; Zhou, Dan; Fan, Li-Zhen
Highlights: A series of FEC-modified composite polymer electrolytes are synthesized. A proper amount of FEC is conducive to promote interfacial stability. LiF produced by FEC has a substantial effect on the solid electrolyte interface. The resultant product delivers excellent rate capability and exceptional cyclability. Abstract: Composite polymer electrolytes (CPEs) with Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) ceramic oxide electrolytes are attracting significant interest because of the merits of LLZTO. However, inadequate solid-solid contact between electrolytes and electrodes invariably results in high interfacial impedance, which is harmful to CPEs' performance. Herein, fluoroethylene carbonate (FEC) additive which possesses excellent ability in guiding uniform Li + deposition and suppressing Li dendrite growth was introduced into the electrolyte, and novel CPEs were successfully prepared. It shows a broad electrochemical window of 5.2 V (vs. Li + /Li), low interface impedance, and a high lithium ion migration number of 0.62. As a result, the assembled symmetrical Li/PHTL-FEC-LLZTO/Li cells can run stably for over 500 h at 0.2 mA cm –2 . Moreover, the Li metal battery with LiFePO4 (LFP) cathode shows superior cyclic stability with a high initial capacity of 132.9 mAh g –1, and a large retention of 88.5% after 200 cycles at 0.5 C. This excellent electrochemical performance of the battery can be attributed to the employment of FEC additives, which endows promising potential in reducing the interface impedance, promoting lithium uniform deposition, and stabling interface performance in the electrolyte. Graphical abstract: Image, graphical abstract Because of the coordination between FEC and Li +, FEC was directed to the broken interface and therefore formed a new LiF-rich layer to cover the damaged location, which enables the interface self-healing of Li-metal, avoiding the formation of Li dendrites and accomplishing a long stable Li deposition.